The effect of tourniquet usage on cement penetration in total knee arthroplasty: A prospective randomized study of 3 methods. Issue 4 (January 2018) - Ozkunt, Okan; Sariyilmaz, Kerim; Gemalmaz, Halil Can; Dikici, Fatih
Abstract: Background: It is a randomized study to compare cement penetration on x-rays after total knee arthroplasty (TKA) among 3 different ways to use tourniquets; application during the surgery, application only with implantation prosthesis and with no tourniquet use. Methods: A total 69 knees of 59 patients were included in the study in a quasirandom manner. Each patient had physical exams and standard radiographic evaluations at 6 weeks after the TKA procedure. Outcome evaluations included visual analog scale (VAS) scores, Knee Society Scores (KSS), blood transfusion, and drainage status after surgery for all groups. For radiographic review, the tibial plateau was divided into zones in the anterior–posterior and lateral views, according to the Knee Society Scoring System. Results: The average age of the patients who were eligible for the study was 65.05 (range 46–81) years. All 59 patients included in the study were female patients. Group 1 consisted of 24 patients who had TKA with use of a tourniquet during the entire operation. Group 2 consisted of 20 patients who had TKA with use of tourniquet only at the time of cementing and group 3 consisted of 25 patients with no use tourniquet. There is no significant difference in early cement penetration among the groups (group 1 2.50 mm, group 2 2.28 mm, group 3 2.27 mm; group 1 vs 2 P = . 083, group 1 vs 3 P = . 091, group 2 vs 3 P = . 073). There is no significant difference for postoperative drainage among the 3 groups (group 1 245 mL, group 2 258.76 mL, group 3 175.88 mL; group 1 vs 2 P = . 081, group 1 vs 3 P = . 072, group 2 vs 3 P = . 054). There was no need to transfuse more than 1 unit in any patient. The VAS score was significantly higher (group 1 3.58, group 2 1.55, group 3 1.52; group 1 vs 2 P = . 022, group 1 vs 3 P = . 018, group 2 vs 3 P = . 062) and KSS was significantly lower in the tourniquet group (group 1 63, group 2 79, group 3 82; group 1 vs 2 P = . 017, group 1 vs 3 P = . 02, group 2 vs 3 P = . 082). Conclusion: We do not suggest long-duration tourniquet use, which can lead higher pain scores and reduce functional recovery after total knee arthroplasty.